In vitro antibacterial activity of Quercus Infectoria gall extracts against multidrug resistant bacteria - Malik, Masrah (Universiti Sains Malaysia, 2013)
Antimicrobial activities of plants have long been evaluated for their potential safe remedies in the future to minimize the unwanted resistance effects of microorganisms. The study was conducted to evaluate the antibacterial activity of Quercus infectoria gall extracts against multidrug resistance (MDR) bacterial clinical isolates by determination of minimum inhibitory concentration (MIC) using the twofold serial microdilution technique at concentration ranging from 5.00 mg/ml to 0.01 mg/ml and minimum bactericidal concentration (MBC) values. Three different concentrations (1, 2 and 5 mg/disc) of aqueous and ethanol extracts of Q. infectoria galls were used for comparison of optimum disc concentration during screening test with five MDR bacterial clinical isolates namely MRSA, MRCoNS, MDR Acinetobacter sp., ESBL E. coli and ESBL K. pneumoniae. We found that, the inhibition zones diameter of 5 mg/disc were significantly larger than inhibition zones diameter of 1 mg/disc aqueous extract against MRSA, MRCoNS and MDR Acinetobacter sp. Similarly, the significant difference of inhibitory zone diameter was observed between 2 mg/disc and 5 mg/disc of aqueous extract against all three isolate strains. For ethanol extract, larger inhibition zones diameter was observed with 5 mg/disc diffusion plate of MRSA and MDR Acinetobacter sp. as compared to 1 mg/disc diffusion plate. Among all tested bacteria, MRCoNS was the most susceptible followed by MRSA during screening. Both extracts showed weak inhibitory effects against MDR Acinetobacter sp. while there was no inhibition zone observed for ESBLs isolates. All of the three concentrations of extracts showed inhibition zone size which was significantly different against MRSA and at 5 mg/disc; there was a significant difference in the zone sizes between both extracts was also observed in MRCoNS (p < 0.05). The MIC and MBC values of the extracts ranged from 0.08 mg/ml to 2.5 mg/ml. The MIC values for aqueous and ethanol extracts against MRSA were 0.08 mg/ml and 0.16 mg/ml respectively whereas the MIC value for both extracts against MRCoNS were the same (0.08 mg/ml). The MBC values of aqueous extracts against MRSA and MRCoNS were above their MIC values whereas the MBC values of ethanol extracts were the same with the MIC values against MRSA and MRCoNS. MBC values of both extracts against all Gram negative bacteria tested were the same with their MIC values; MDR Acinetobacter sp. (0.63 mg/ml), ESBL E. coli (2.50 mg/ml) and ESBL K. pneumoniae (1.25 mg/ml). The Q. infectoria gall extracts may be considered as a potentially good source of antimicrobial agents due to the effectiveness in their in vitro antibacterial activity against MDR bacteria.